Hexavalent Chromium Detoxification and Bioremediation by Bacillus sp. from Tannery Effluents - Fatima Anjum,; Afifa,; Muhammad Faisal,; Muhammad Hidayat Rasool, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
This study examined the Cr(VI) absorption mechanism in indigenous Cr(VI)-tolerant bacterial strains. Five potential chromium-resistant bacterial strains were isolated indigenously from tannery effluent later identified as Bacillus sp. using phenotypic and genotypic techniques. In nutrient-rich media, Nutrient Agar, the concentration of Cr was analyzed for maximum tolerance (100 - 1500 µg/ml), and found that the strains showed growth even at 1500 µg/ml. Diphenylcarbazide (DPC) assay was performed to analyze the ability of chromium-reducing bacteria to reduce Cr under various conditions, such as pH, temperature, Cr(VI) content, incubation time, and inhibitors such as antibiotics and heavy metals (Ag, Ni, Zn, Mn and Co). In pilot research, Bacillus licheniformis (YAK4) and Bacillus endophyticus (YAK7), removed up to 95% Cr(VI) from tannery wastewater in 8 days. The obtained microbial-cleansed water was used afterward in a pot experiment to grow Vigna radiata and proved to be useful for the growth of plants. Capacitive heavy metal tolerance and Cr(VI) reduction potentials makes Bacillus licheniformis and Bacillus endophyticus an ideal option for decontaminating a Cr(VI) contaminated environment.